2023
DOI: 10.18203/2394-6040.ijcmph20230614
|View full text |Cite
|
Sign up to set email alerts
|

Vending environment and hygiene practices of street food vendors in an out of campus food environment in Kenya

Abstract: Background: Street foods (SF) are ready-to-eat foods and the safety and hygiene practices of street food vendors (SFVs) are important in the prevention of food-borne diseases (FBD). This study assessed the food handling practices and vending environments of SFVs operating outside a public university (Chuka University) in Ndagani, Kenya. Methods: The study used an observational cross-sectional design where SFVs were observed during data collection. Census sampling was used to recruit 100 SFVs in Ndagani, Kenya.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the safety and hygiene of these foods have raised significant public health concerns. Street food vendors often have inadequate food safety and hygiene knowledge and practices, which can pose hazards to consumers [1,2]. Additionally, it has been reported that street food consumers (SFCs) have little knowledge about food safety, which further increases the risks associated with consuming street-vended foods [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the safety and hygiene of these foods have raised significant public health concerns. Street food vendors often have inadequate food safety and hygiene knowledge and practices, which can pose hazards to consumers [1,2]. Additionally, it has been reported that street food consumers (SFCs) have little knowledge about food safety, which further increases the risks associated with consuming street-vended foods [3].…”
Section: Introductionmentioning
confidence: 99%